Avaliação da DPOC em tabagistas com suspeita de isquemia miocárdica - Nascimento Junior, Marcos Gabriel do (2017)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is one of the main causes of morbidity and mortality in adults over 40 years old, characterized by airflow limitation and inflammation, with several systemic manifestations. Its main comorbidity is cardiovascular disease, which is responsible for a high impact on the prognosis and mortality of patients with this disease. The objective of this research was to compare smokers with and without COPD, required for suspicion of myocardial ischemia. Methods: The study population consisted of individuals submitted to Physical Stress Echocardiography (EEEF) for the diagnosis of myocardial ischemia, clinically investigated and submitted to pulmonary function examination to diagnose COPD. A total of 267 smokers were enrolled in a G1 group: those with a diagnosis of COPD with 121 participants (45%), 63.6% with mild COPD, according to GOLD criteria (2017); And group G2: without COPD with 146 participants (55%).Results: The presence of myocardial ischemia was significantly different between the groups (p<0.001), independently of the variables common to smokers and the classification of the disease. Statistically important was also the presence of comorbidities in the G1 group (osteoporosis, depression and neoplasms). It is concluded that in individuals with suspected myocardial ischemia, the investigation of COPD is fundamental, since its presence is statistically higher in smokers with COPD criteria, even in the initial phase.